The Influence of Project-Based Learning Model on Ability to Find Research Problems in Learning Strategy Courses - Chamisijatin, Lise; Zaenab, Siti; Permana, Fendy Hardian (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2023)
Teaching competence requires several skills in the form of real products or works, so in lectures Learning Strategies are very suitable for using the Project-Based Learning (PjBL) model. This study aims to describe the effect of using a project-based learning model on the ability to find problems. This research is a pre-experimental study and uses a single group design with pretest â€“ treatment â€“ posttest. The design steps are as follows: (1) Selecting a group of subjects for the sample, (2) Conducting a pretest, (3) Providing treatment, (4) Providing a posttest after treatment, (5) Finding the average score and standard deviation, both from pretest and posttest compare the two, and (6) test the average difference. The subjects of this study were second semester students of the Department of Biology Education, Faculty of Teacher Training and Education, Universitas Muhammadiyah Malang who took part in the Learning Strategy course (38 students). Data collection techniques were carried out by pretest and posttest. The research instruments used were pretest and posttest questions, and rubric sheets to assess students’ assignments in finding problems. Data analysis for knowledge was performed by paired t test. Based on the results of the analysis, it shows that tcount > ttable (31.78 > 2.02619), which means that there is a significant difference, so that the development of the PjBL model has an effect on the ability to find research problems in the Learning Strategy course.